Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, dan Komisaris Independen terhadap Financial Distress dengan Leverage sebagai Variabel Moderasi - Nugraha, I Nengah Adi; Wirajaya, I Gde Ary (Owner : Riset dan Jurnal Akuntansi, 2024)
Financial distress conditions have a bad impact on a company, where companies experiencing financial distress conditions can lose the trust of parties who have a relationship with the company. This study aims to analyze and describe the effect of institutional ownership, managerial ownership and independent commissioners on financial distress with leverage as a moderating variable. The population of this study consisted of 86 property and real estate companies for the period 2018-2021 listed on the Indonesia Stock Exchange (IDX). The collection method used was purposive sampling, and 40 company samples were selected. The data analysis technique applied in this study is multiple linear regression analysis and Moderating Regression Analysis (MRA) using IBM SPSS. The results of hypothesis testing show that institutional ownership has a positive effect on financial distress, while managerial ownership and independent commissioners have a negative effect on financial distress. The results of the moderation test in this study indicate that leverage is unable to moderate the effect of institutional ownership, managerial ownership and independent commissioners on financial distress.